Determination of craniofacial relation among the subethnic Indian population: A modified approach - (Sagittal relation) - A Sumathi Felicita; Shyamala Chandrasekar; K K Shanthasundari (Wolters Kluwer Medknow Publications, 2012)
Aim : To measure the linear cephalometric dimensions of anterior and posterior segments of the craniofacial complex sagittally, to establish ratios between different linear dimensions of sagittal segments and check for dimensional balance among the various segments in subjects with normal occlusion, pleasing profile and facial harmony. Setting and Sample Population : Department of Orthodontics, Saveetha University. Lateral cephalograms of 120 subjects of both sexes in the age group of 17-28 years with normal occlusion belonging to Chennai, India Materials and Methods : Linear dimensions of anterior and posterior segments of the craniofacial complex were measured sagittally with the posterior maxillary plane as a key reference plane. Ratios were established between the various parameters in the anterior and posterior region. Results : A ratio of 1:1 was found to exist between the individual and aggregate sagittal segments of the craniofacial complex in both sexes. There was a statistically significant sexual dimorphism in the aggregate lengths(P=0.028,P=0.005).However, the ratio between the anterior cranial floor and effective maxillary length was 2:3 and 5:8 and that between anterior cranial floor to effective mandibular length was 5:8 and 3:5 in females and males respectively. The difference in the above values was not statistically significant. Conclusion : A dimensional balance was found to exist between the maxilla and mandible both at the dentoalveolar and skeletal level with a ratio of 1:1. There was also a dimensional balance between the posterior cranial floor and ramus width. However, there was no architectural balance between the anterior cranial floor and maxilla and mandible.